Pengaruh Customer Experience dan Brand Image terhadap Customer Satisfaction serta Dampaknya pada Customer Loyalty - Rita, Rita; Trimulyani, Fabiola Meike (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
PT Bluebird Tbk is a company engaged in the field of transportation services. This study uses quantitative methods through purposive sampling data collection techniques with 100 respondents who are Bluebird Taxi users and domiciled in Greater Jakarta. Data collection using questionnaires and analyzed through SmartPLS software. The analysis is used to test the validity and reliability. The aim is to determine the effect of customer experience and brand image on customer satisfaction and its impact on customer loyalty. Data analysis uses structural equation modeling (SEM) with partial least square approach. The results showed that customer experience and brand image had a significant effect on customer satisfaction, while customer experience and brand image did not significantly effect customer loyalty from the path coefficient results.